Randomized controlled trial of acupuncture for prevention of radiation‐induced xerostomia among patients with nasopharyngeal carcinoma - Meng, Zhiqiang; Garcia, M. Kay; Hu, Chaosu; Chiang, Joseph; Chambers, Mark; Rosenthal, David I.; Peng, Huiting; Zhang, Ying; Zhao, Qi; Zhao, Genming; Liu, Luming; Spelman, Amy; et al. (Cancer, 2012)
BACKGROUND: Xerostomia (dry mouth) after head/neck radiation is a common problem among cancer patients, and available treatments are of little benefit. The objective of this trial was to determine whether acupuncture can prevent xerostomia among head/neck patients undergoing radiotherapy. METHODS: A randomized, controlled trial among patients with nasopharyngeal carcinoma was conducted comparing acupuncture to standard care. Participants were treated at Fudan University Shanghai Cancer Center, Shanghai, China. Forty patients were randomized to acupuncture treatment and 46 to standard care. Patients were treated 3×/wk on the same days they received radiotherapy. Subjective measures included the Xerostomia Questionnaire and MD Anderson Symptom Inventory‐Head and Neck (MDASI‐HN). Objective measures were unstimulated and stimulated whole salivary flow rates. Patients were followed for 6 months after the end of radiotherapy. RESULTS: Xerostomia Questionnaire scores for acupuncture were statistically significantly lower than for controls starting in week 3 through the 6 months (P = .003 at week3, all other P < .0001), with clinically significant differences as follows: week 11, relative risk (RR) 0.63 (95% confidence interval [CI], 0.45‐0.87); 6 months, RR 0.38 (95% CI, 0.19‐0.76). Similar findings were seen for MDASI‐HN scores. Group differences emerged as early as 3 weeks into treatment for saliva (unstimulated whole salivary flow rate, P = .0004), with greater saliva flow in the acupuncture group at week 7 (unstimulated whole salivary flow rate, P < .0001; stimulated whole salivary flow rate, P = .002) and 11 (unstimulated whole salivary flow rate, P < .02; stimulated whole salivary flow rate, P < .03) and at 6 months (stimulated whole salivary flow rate, P < .003). CONCLUSIONS: Acupuncture given concurrently with radiotherapy significantly reduced xerostomia and improved quality of life. Cancer 2011. © 2011 American Cancer Society. The authors conducted a randomized, clinical trial of acupuncture to decrease the development of xerostomia in patients undergoing radiation for nasopharyngeal carcinoma. Acupuncture given concurrently with radiotherapy significantly reduces xerostomia and improves quality of life during radiotherapy and 1 and 6 months later.